"Killing nature—killing us": "Cultural threats" as a fundamental framework for analyzing Indigenous movements against mining in Siberia and the Russian North. Issue 3 (4th May 2023) - Plotnitskiy, Andrey; Roy Chowdhury, Arnab
ABSTRACT: The Shor people are protesting the ongoing mining of coal in the southern Kemerovo region of Siberia, while the Izhma Komi people are contesting the extraction of oil in the northern Komi Republic (Northwestern Federal District). The theory of "political opportunities" states that movements emerge when opportune moments create spaces for these, but we argue that in illiberal spaces, movements emerge against "threats" in an ever-decreasing political space. We argue that the extraction of coal and oil in Russia's eastern regions poses not only structural threats – economic problems, public health/environmental decline, erosion of rights, and state repression – to its Indigenous peoples, but also cultural threats to their livelihoods and life-worlds. The various structural threats are thus intertwined with cultural threats in the case of Indigenous rights movements, and environmental decline is inextricably bound with the erosion of rights.